1983
DOI: 10.1037/0022-3514.45.4.839
|View full text |Cite
|
Sign up to set email alerts
|

Personality and social resources in stress resistance.

Abstract: This study examined personality, social assets, and perceived social support as moderators of the effects of stressful life events on illness onset. In a group of 170 middle and upper level executives, personality hardiness and stressful life events consistently influenced illness scores, the former serving to lower symptomatology, the latter to increase it. Perceived boss support had its predicted positive effect. Executives under high stress who perceived support from their supervisors had lower illness scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
305
2
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(342 citation statements)
references
References 19 publications
(33 reference statements)
24
305
2
11
Order By: Relevance
“…Psychologically "brittle" children, by contrast, exhibited behavioral problems, depressive symptoms, and higher levels of drug use in adolescence (Block, Block, & Keyes, 1988;Block & Gjerde, 1990). Studies of diverse populations have also empha-sized the inherent flexibility of trait resilience in adulthood: Psychologically resilient or "hardy" adults appear to be those who are committed to what they were doing, in control of their problems, and willing to accept changes in life as challenges to be mastered rather than threats to be endured (Kobasa, 1979;Kobasa, Maddi, & Kahn, 1982;Kobasa & Puccetti, 1983;Maddi, Bartone, & Puccetti, 1987).…”
Section: Trait Resilience and Bereavementmentioning
confidence: 99%
“…Psychologically "brittle" children, by contrast, exhibited behavioral problems, depressive symptoms, and higher levels of drug use in adolescence (Block, Block, & Keyes, 1988;Block & Gjerde, 1990). Studies of diverse populations have also empha-sized the inherent flexibility of trait resilience in adulthood: Psychologically resilient or "hardy" adults appear to be those who are committed to what they were doing, in control of their problems, and willing to accept changes in life as challenges to be mastered rather than threats to be endured (Kobasa, 1979;Kobasa, Maddi, & Kahn, 1982;Kobasa & Puccetti, 1983;Maddi, Bartone, & Puccetti, 1987).…”
Section: Trait Resilience and Bereavementmentioning
confidence: 99%
“…An initial pool of 128 expressions in Spanish was derived from survivors' testimonies and expert consensus corresponding to (a) basic beliefs, (b) signs of subjective damage, resilience and growth, (c) ways of social, cognitive and behavioural appraisal and processing of extreme experiences (Pérez-Sales, 2006) and an extensive review of existing models and measures on the impact of extreme experiences (Antonovsky, 1987;Calhoun & Tedeschi, 1999;Ehlers & Clark, 2000;Epstein, 1989;Janoff-Bulman, 1992;Kauffman, 2002;Kobasa, 1983;Pennebaker, 1990;Stroebe, Schut, & Finkenauer, 2000), ethnographic and qualitative studies (Lifton, 1967;Pérez-Sales, Bacic, & Durán, 1998) or autobiographical accounts of victims' experiences (Amery, 2001;Frankl, Lasch, & Allport, 1963;Levi, 1987;Steinberg, 2001). 80 items were suitable for the general population, 48 were meaningful only for survivors.…”
Section: Methodsmentioning
confidence: 99%
“…Further, shared leadership in teams have been found to contribute to higher performance than vertical leadership in many cases (Wang, Waldman & Zhang, 2014). Choi, Sung & Kim (2010) and Kobasa & Puccetti (1983) found that support from higher-level managers played a key role in overcoming major challenges. However, Arman, Wikström & Dellve (2009) pointed out that Healthcare managers spend a relatively small amount of time with their own senior managers.…”
Section: Social Supportmentioning
confidence: 99%